HANNAH ARENDT AND THE FACULTY OF THINKING - A PARTNER TO THINK, A WITNESS TO ACT - Assy, Bethânia (Revista Ética e Filosofia Política, 2018)
The intriguing paradoxical condition of the faculty of thinking allows “the mind to withdraw from the world without ever being able to leave it or transcend it.” It justifies in the first place the use of metaphorical language, imagination and re-presentation, to quote the terms Arendt uses to articulate the imbrications among thinking, judging, speech, and the visible world. Either in silent critical thought or in judgment, what is at stake are the outlooks and events of the appearing world transposed into ordinary language. In the case of thinking activity, a silent “conceptual metaphorical speech” turns to be its adequate operation, since thinking “must prepare the particulars given to the sense in such a way that the mind is able to handle them in their absence; it must, in brief, de-sense them.” Thinking is already conceived into speech before it is communicated, spoken out and understood by others. Likewise, thinking requires this same visibility of being heard and understood by others, “just as a creature endowed with the sense of vision is meant to see and to be seen. Thought without speech is inconceivable; ‘thought and speech anticipate one another. They continually take each other’s place.’” Thought derives from human beings lived experience and therefore must remain tied to them.